Can Personalized Nudges Improve Learning in Hybrid Classes? Experimental Evidence From an Introductory Undergraduate Course. Issue 2 (3rd April 2018) - O'Connell, Stephen D.; Lang, Guido
Abstract: A field experiment was conducted to investigate whether personalized e-mail reminders can improve study consistency and learning outcomes in an introductory-level undergraduate course. By randomly assigning whether nearly 300 students would receive occasional e-mail messages encouraging out-of-class study, we find that these reminders increased exam performance by 0.2 standard deviations. Using detailed information on the timing and duration of study effort, we find two distinct patterns explaining this increase. Reminders increased weekend study time slightly, and weekday studying remained constant although it was shifted approximately 2 to 3 hours earlier for those who received reminders. A follow-up survey corroborates these channels, and suggests a third mechanism: increased cognitive effort during study. These findings highlight the potential for low-cost behavioral interventions to improve student performance. (Keywords: e-mail reminders; personalized nudges; hybrid learning; higher education)